Biosynthesis and Synthesis of Griseoviridin and Viridogrisein - Xu, Leyan; Renata, Hans (Synthesis)
Griseoviridin and viridogrisein are synergistic type A/B streptogramin antibiotics that cooperatively inhibit protein translation in Gram-positive pathogens. This review provides an overview of their discovery and bioactivity and highlights key biosynthetic and synthetic advances that have enabled analog development to address antibiotic resistance. The review is organized into five sections: 1 Introduction 2 Structural assignment and biological studies 3 Biosynthesis 4 Synthesis 5 Conclusion